A one-year follow-up of the cognitive and psycho-behavioural skills in artistic gymnastics. (May 2023) - Laureys, Felien; Collins, Dave; Deconinck, Frederik J.A.; Vansteenkiste, Pieter; Lenoir, Matthieu
Abstract: A good set of cognitive and psycho-behavioural skills are beneficial for young athletes to overcome and benefit from developmental challenges. Unfortunately, there is still a dearth of knowledge on how both these cognitive (i.e., executive functions; EF) and psycho-behavioural (i.e., psychological characteristics of developing excellence; PCDE) skills develop in youth athletes. Especially for athletes in early specialisation sports such as artistic gymnastics, the early EF and PCDE development might be important to be able to cope with the pressure and challenges that comes with a transition to the next stage. In the current study, artistic gymnasts between 9 and 22 years old were tested twice with a 12-month interval to investigate the changes in EF and PCDE. Results showed that EF developed within the youngest stage, but plateaued at the later stages. Most PCDE did not seem to change over time within each stage. Furthermore, the transition to a new stage does not seem to coincide with an increased improvement of PCDE. However, with a case study approach in the oldest stages, still inter-individual differences in EF and PCDE scores over time were observed. This study shows that EF and PCDE develop over time, albeit in a non-linear way, and along a variety of developmental trajectories. Highlights: Executive functions of artistic gymnasts develop at the same rate as a normal population. Psycho-behavioural skills did not seem to develop over time on average. A case-study approach highlighted inter-individual differences on mental skills. The nonlinear, inter individual developmental trajectories are highlighted.